Determining the Effect of Dietary Habit of Phosphorus Intake in Chronic Kidney Disease Patients on Haemodialysis: A Prospective and Observational Study - Vajed Mogal (Research Highlights in Disease and Health Research Vol. 2, 2023)
Background: Phosphorus is an essential nutrient required for multiple physiological functions; recent researchers found that high phosphorus intake could have detrimental effects on health. Hyperphosphatemia is one of the most important risk factors for morbidity and mortality for chronic kidney disease (CKD) patients. The purpose of this chapter are to study the effect of dietary habits on dietary phosphorous intake in chronic kidney disease patients on hemodialysis, to study the prevalence of hyperphosphatemia in patients of CKD on maintenance hemodialysis, and tto see the impact of dietary control of phosphorus in CKD patients. This cross sectional comparative study was conducted at a tertiary care centre in western region Maharashtra state, India. A total of 80 patients with CKD on maintenance hemodialysis were chosen for the study; patients on maintenance hemodialysis twice a week for four hours. The findings showed that there was a significance difference between the pre and post phosphorus of group A experimental group. Age groups 20 to 40 and 40 to 60 showed the greatest differences, whereas groups 60 to 80 showed no differences. Group B, where the age range of 60 to 80 has demonstrated positive response, also showed a significant change in pre and post phosphorus. Renal diet education can lower phosphorus levels, and guided diet education can help control hyperphosphatemia in haemodialysis patients. The study’s goal is to see how dietary habits affect dietary phosphorus intake in CKD patients on hemodialysis. Dietary counselling promotes the consumption of foods containing the least amount of inorganic or absorbable serum phosphorus, a low phosphorus-to-protein ratio, and an adequate protein content. Our phosphorus additives list aids in lowering phosphorus intake indirectly. A younger group of patients successfully followed a renal diet for hyperphosphatemia.